Addie Model: Development of Anti-Corruption Education Materials in Elementary School - Suyantiningsih, Suyantiningsih; Rahmadonna, Sisca (KnE Social Sciences, 2019)
This study aims to develop anti-corruption education materials based on integrity values for elementary school students in Yogyakarta. This research is a research and development using ADDIE (Analyze, Design, develop, implement, evaluate) development models. Data was obtained through literature studies, observation, interviews, and Focus Group Discussion (FGD) which were then processed descriptively qualitative. The results showed that the ADDIE model used to develop the material illustrates that the integrity value that is most needed to be developed in anti-corruption education for elementary school students is the value of honesty and simplicity, this is obtained from the analysis in the development of ADDIE and reinforced by the answers given by the teacher during FGD, where 31.50% of teachers chose honesty values and 23.3% of teachers chose the value of simplicity. Keywords: ADDIE Model; Anti-Corruption Education; Elementary Schools’ Students